Instrumentos náuticos inventados por Juan de Herrera para determinar la longitud de un lugar - Cervera Vera, Luis (1997)
Navigator's difficulty in calculating the longitude of a place was resolved by Juan de Herrera using nautical instruments which he had invented. He asked Felipe II for the necessary licence to manufacture them, and this was granted by the monarch following a favourable report from the Council of the Indies. With the instruments available, the King ordered them to be used by the Armada of Galleons. For Herrera, this represented the satisfaction of his scientific recognition, though he received no financial benefit for his invention.